Archaean andesite petrogenesis : insights from the Grædefjord Supracrustal Belt, southern West Greenland - Szilas, Kristoffer; Hoffmann, Elis; Scherstén, Anders; Kokfelt, Thomas; Münker, Carsten (Precambrian Research, 2013)
We present new whole-rock major, trace and platinum-group element data, as well as Sm–Nd and Lu–Hfisotope data for meta-volcanic rocks from the Mesoarchaean Grædefjord Supracrustal Belt (GSB), locatedwithin the Tasiusarsuaq terrane, southern West Greenland. We also present new in situ zircon U–Pbisotope data (by LA-ICP-MS) for associated felsic rocks. This region has experienced amphibolite to lowergranulite facies metamorphism, causing re-equilibration of most mineral phases (including zircon).An intrusive tonalite sheet with a zircon U–Pb age of 2888 ±6.8 Ma, yields a minimum age for the GSB.The Sm–Nd and Lu–Hf isotope data do not provide meaningful isochron ages, but the isotope compositionsof the mafic rocks are consistent with the ca. 2970 Ma regional volcanic event, which is documented in pre-vious studies of the Tasiusarsuaq terrane. The major and trace element data suggest a significant crustalcontribution in the petrogenesis of andesitic volcanic rocks in the GSB. The trace element variation of theseandesitic leucoamphibolites cannot be explained by bulk assimilation–fractional-crystallisation (AFC)processes involving local basement. Rather, the observed patterns require binary mixing between basalticand felsic end-member magmas with between 50% and 80% contributions from the latter (depending onthe assumed felsic composition). Hf-isotope constraints point to contamination with pre-existing conti-nental crust with an age of ca. 3250 Ma. Basement gneisses of this age were previously described at twolocalities in the Tasiusarsuaq terrane, which supports the mixing hypothesis. Thus the felsic end-memberlikely represents melts derived from the local basement.Ultramafic rocks (18.35–22.80 wt.% MgO) in GSB have platinum-group element (PGE) patterns that aresimilar to magmas derived from high-degree melting of mantle, but they have relatively enriched traceelement patterns. We propose that the ultramafic rocks represent arc-related picrites or alternativelywere derived by melting of metasomatised ...